(untitled) (Eduscotech, 2022)
Improving the quality of education through improving the quality of learning is one way that can be taken in an effort to improve the quality of education in schools. Improving the quality of learning also has a strategic meaning and has a positive impact, in the form of (1) increasing the ability to solve real educational and learning problems, (2) improving the quality of inputs, processes and learning outcomes, (3) increasing the professionalism of educators, and (4 ) application of researchbased learning principles. In accordance with the background of the problem, the problem can be formulated as follows "How to Improve the Teaching Quality of Class III Teachers through Upgrading Learning Model Development at SDN Kalibatur 4 Kalidawir District, Tulungagung Regency in 2022? The purpose of this study is to obtain an objective picture of Improving the Teaching Quality of Class III Teachers through Upgrading Learning Model Development at SDN Kalibatur 4, Kalidawir District, Tulungagung Regency in 2022. This School Action Research (PTS) was carried out at the school where the researcher was the principal, namely SDN Kalibatur 4 with the research subject being 1 class III teacher. The name of the research subject is Retno Nurwanti, S.Pd. elementary school. The reason for choosing this subject is because the teaching skills of Class III teachers are still low, especially in applying the Up Grading Learning learning model. Upgrading Learning has a learning meaning that helps teachers connect subjects with real-world situations and learning that motivates students to connect their knowledge and applications with everyday life as family and community members (Kasihani, 2001). Based on the results of this study, it can be concluded that the implementation of Up Grading Learning Model Development by the Principal is able to improve the Teaching Quality of Class III Teachers at SDN Kalibatur 4, Kalidawir District, Tulungagung Regency in 2022. In the implementation of the first cycle of research, the average percentage of teacher activities obtained was Rp. 70.00% increased in the second cycle to 82.50%. While student activity in the first cycle of 75.00% increased in the second cycle to 85.00%.